The influence of management support, computer anxiety and enjoyment on science teachers' perception of the use of digital technologies in Hail primary school : a survey - Al-Shammari, Khalid Abdalmohsen F (Kulliyyah of Education, International Islamic University Malaysia, 2015)
This research sought to identify the availability of digital technologies in public primary schools in Hail, Saudi Arabia and their use in teaching science subjects from the viewpoints of science teachers in the city. Another primary focus of this research was to address the applicability of TAM. A total of 330 Science teachers (145 males and 185 females) were drawn from a stratified sample randomly. Two instruments were developed to collect data; the first instrument was a self-developed checklist to profile the data related to the availability of digital technologies and facilities and the second instrument was a questionnaire adopted from three previous studies. The findings indicated an acute lack in the availability of digital technology facilities in all the primary schools surveyed, both boys' schools and girls'. Teachers' use of digital technologies in teaching and learning is influenced by several factors, namely schools' management support (MS), computer anxiety (CA) and enjoyment (E). The availability of digital technological facilities varied throughout the primary schools in Hail. Throughout the 12 digital technology facilities investigated in the study, only 4 were accessible in all the schools. This research would assert that management support (MS) and enjoyment (E) on Science teachers are positively correlated with perceived usefulness (PU) relative to digital technology usage. Moreover, it would further assert that (CA) on Science educators is negatively correlated to PE with regards to digital technology usage. The study found that the intention to use (IU) influenced Science teachers' actual use (AU) of digital technologies in primary schools. It was also found that perceived ease of use (PE) and enjoyment (E) influence Science teachers' intentions in making use of digital technologies in primary schools. But perceived usefulness (PU) seems to not influence Science teachers' intentions to apply digital technologies in primary schools. Science teachers are more likely to be concerned with the ease of use in digital technology and enjoyment in making decisions to use the technology for teaching, as opposed to how digital technology would facilitate better education and learning through their use. The research proposed an extension to the TAM model that accounts for the utilization of the unified model within the MS, CA, E, PE, PU, IU and AU contexts. The results showed that the TAM structure directly impacts the MS, CA, E, PE, PU, IU and AU contexts. These results demonstrate the success of the proposed extension in achieving the objectives of this study. This study will contribute to decision-making to disseminate digital technologies adoption among Science teachers in the primary schools and is beneficial to specialists in teacher training, and those in charge of their training in digital technologies.